Developing Country Agriculture and the New Trade Agenda - Hoekman, Bernard M. 1959- (The World Bank, 1999)
May 1999 - In the new round of World Trade Organization talks expected in late 1999, negotiations about access to agricultural and services markets should be given top priority, but new trade agenda issues should also be discussed. Including new trade agenda issues would increase market discipline's role in the allocation of resources in agriculture and would encourage nonagricultural groups with interests in the new issues to take part in the round, counterbalancing forces favoring agricultural protection. A new round of World Trade Organization negotiations on agriculture, services, and perhaps other issues is expected in late 1999. To what extent should those negotiations include new trade agenda items aimed at ensuring that domestic regulatory policies do not discriminate against foreign suppliers? Hoekman and Anderson argue that negotiations about market access should be given priority, as the potential welfare gains from liberalizing access to agricultural (and services) markets are still huge, but new issues should be included too. Including new trade agenda issues would increase the role of market discipline in the allocation of resources in agriculture and would encourage nonagricultural groups with interests in the new issues to take part in the round, counterbalancing forces in favor of agricultural protection. They also argue, however, that rule-making efforts to accommodate the new issues should be de-linked from negotiations about access to agricultural markets, because the issues affect activity in all sectors. This paper-a product of the Development Research Group-is part of a larger effort in the group to analyze options and priorities for developing countries in the run-up to a new round of WTO negotiations. Bernard Hoekman may be contacted at bhoekman@worldbank.org or kanderson@economics.adelaide.edu.au